Impact of calcification and infrapopliteal outflow on the outcome of endovascular treatment of femoropopliteal occlusive disease. (February 2019) - Athayde Soares, Rafael de; Matielo, Marcelo Fernando; Brochado Neto, Francisco Cardoso; Pires, Ana Paula Maia; de Almeida, Rogério Duque; de Jesus Martins, Murilo; Sacilotto, Roberto
Objectives: In this paper, we report the long-term outcomes of the endovascular treatment of femoropopliteal occlusive disease, focusing on the importance of calcification and runoff outflow on limb salvage and patency, and the factors associated with these outcomes at a single center. Methods: This retrospective cohort study included consecutive patients with femoropopliteal occlusive who underwent femoropopliteal angioplasty at the Division of Vascular and Endovascular Surgery, Hospital do Servidor Público Estadual, São Paulo, Brazil, between January 2015 and July 2017. Results: In total, 86 femoropopliteal occlusive angioplasties were performed in 86 patients, with an initial technical success rate of 95.34%. The mean ± standard deviation follow-up time was 880 ± 68.84 days. The analysis was performed at 720 days. Technical failure occurred in four patients, who were excluded from the analysis, leaving 82 patients and 82 femoropopliteal occlusive angioplasties. The estimated primary patency, secondary patency, limb salvage, and overall survival rates at 720 days were 60%, 96%, 90%, and 82.5%, respectively. In univariate and multivariate analyses, Cox regression showed worse primary patency rates in patients with one tibial vessel or isolated popliteal artery runoff ( p = 0.005), calcification grade 4 ( p = 0.019), calcification grade > 2 ( p = 0.017), small vessel diameter < 4 mm ( p = 0.03) or primary angioplasty without stenting ( p = 0.021). A univariate analysis showed worse limb salvage in patients with one tibial vessel or isolated popliteal artery runoff ( p = 0.039). Conclusions: In this study, the main factors associated with worse outcomes in the endovascular treatment of femoropopliteal occlusive in terms of loss of primary patency were one tibial vessel or isolated popliteal artery runoff, calcification grade 4, or calcification grade > 2, small vessel diameter < 4 mm, and no stents use. One tibial vessel or isolated popliteal artery runoff was also associated with limb loss in a univariate Cox regression analysis.